The theories of regionalism and the future of multiregional organizations. Interview with José Antonio Sanahuja - Romero Cevallos, Marco (2017)
The Spanish political scientist and internationalist, José Antonio Sanahuja, was at the Universidad Andina Simón Bolívar invited by the integration chair Germanico Salgado, to participate in the international seminar Which regional architecture for South America ?, with his master lecture called Broken mirrors: the crisis of European construction and the new paths of Latin American regionalism. José Antonio Sanahuja is a professor and researcher at the Unversidad Complutense de Madrid and Director of the Complutense Studies Institute of International Studies. He is also a specialist in Development Cooperation, European Union-Latin America relations and regionalism and Latin American integration, topics on which he has published numerous books and articles in specialized journals.